1958
DOI: 10.1172/jci103583
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem Forearm Plethysmograph for Study of Acute Responses of the Peripheral Veins of Man: The Effect of Environmental and Local Temperature Change, and the Effect of Pooling Blood in the Extremities1

Abstract: The primary mechanism of action of the smooth muscle of the veins upon their contained blood is one of imparting pressure to the blood by a surrounding force. This mode of action is to be distinguished from that of the smooth muscle of the arterioles, which is one of maintenance of arterial pressure through resistance to the outflow of blood. The function of the arterioles as resistive elements in the circulation is evaluated by the relationship between the volume of the flow of blood through the arterioles pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

1960
1960
1994
1994

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 13 publications
(12 reference statements)
1
42
0
Order By: Relevance
“…Pertinent to this possible explanation of the data obtained are those studies which have demonstrated that venous tone in man is not constant, but may be altered by a variety of stimuli (30)(31)(32)(33)(34). In particular, ganglionic blockade produces venodilatation in patients in congestive heart failure (35,36) and in normal subjects during muscular exercise (34).…”
Section: Discussionmentioning
confidence: 92%
“…Pertinent to this possible explanation of the data obtained are those studies which have demonstrated that venous tone in man is not constant, but may be altered by a variety of stimuli (30)(31)(32)(33)(34). In particular, ganglionic blockade produces venodilatation in patients in congestive heart failure (35,36) and in normal subjects during muscular exercise (34).…”
Section: Discussionmentioning
confidence: 92%
“…This was to insure that the subjects were comfortable but cool. We specifically did not want to induce venodilation or arteriolar dilation by having the subjects in a warm environment (23). A single strand mercury-inrubber strain gauge (24) was utilized for measurements of forearm venous tone and blood flow as described below.…”
Section: Introductionmentioning
confidence: 99%
“…Dilatation is likely to be limited by the degree of resting tone in the veins; when this is overcome, no further venodilatation is possible. In their study of the physiology of forearm veins Wood & Eckstein [11] state that under normal laboratory conditions these vesels have no resting tone. Lack of basal tone was also demonstrated in the studies of Greenfield & Patterson [12].…”
Section: Discussionmentioning
confidence: 99%